The Urgency of Regulatory Accountability for Protecting Victims of Sexual Violence in Cyberspace - Pratama, Muhammad Yusuf Isa; Putri, Hanuring Ayu Ardhani; Nurwanti, Yulian Dwi (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2025)
The advancement of digital technology has contributed to a rise in incidents of sexual violence, particularly those perpetrated through electronic media. This study aims to examine the urgency and effectiveness of the Electronic Information and Transactions (ITE) Law and the Law on the Crime of Sexual Violence (TPKS Law) in providing legal protection for women who are victims of digital sexual violence. It also explores the challenges in implementing these regulations and offers recommendations for strengthening the existing legal framework. Employing a normative legal approach, the study finds that although both laws offer a foundational legal basis, their implementation remains hindered by entrenched patriarchal norms, low levels of digital literacy, and limitations in law enforcement capacity. The study concludes that enhancing legal protection necessitates the development of responsive regulatory measures, secure reporting mechanisms, and improved capacity among law enforcement personnel, alongside greater public awareness. The findings underscore the need to reform the legal protection system to ensure it effectively prioritizes the rights of victims.